Genome Sequence of Fusarium oxysporum f. sp. matthiolae, a Brassicaceae Pathogen - Yu, Houlin (Mol Plant Microbe Interact, 2020)
The filamentous fungus Fusarium oxysporum is a soil-borne pathogen of many cultivated species and an opportunistic pathogen of humans. F. oxysporum f. sp. matthiolae is one of three formae speciales that are pathogenic to crucifers, including Arabidopsis thaliana, a premier model for plant molecular biology and genetics. Here, we report a genome assembly of F. oxysporum f. sp. matthiolae strain PHW726, generated using a combination of PacBio and Illumina sequencing technologies. The genome assembly presented here should facilitate in-depth investigation of F. oxysporum-Arabidopsis interactions and shed light on the genetics of fungal pathogenesis and plant immunity.